2011
DOI: 10.1021/je2002978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shear Rate, Temperature, and Polymer Composition on the Shear Stress of Polyethersulfone/1-Methyl-2-pyrrolidone Cast Solutions

Abstract: Polyethersulfone (PES) is extensively used for the preparation of hollow fiber membrane contactors; these modules are utilized in microfiltration (MF), ultrafiltration (UF), and gas separation. Viscosity plays a crucial role in the fabrication of hollow fiber membranes and their separation performance. In this study the effect shear rate, temperature, and polymer composition on shear stress of dope solutions prepared from PES polymer, dissolved in 1-methyl-2-pyrrolidone (NMP) solvent, is experimentally investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, two rheological tests, (1) constant-stress viscosity and (2) dynamic oscillatory shear tests as a function of temperature, were used to investigate the thermal transition of the copolymers. It has been reported that polymer solutions are very sensitive to shear rate around their phase transition [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two rheological tests, (1) constant-stress viscosity and (2) dynamic oscillatory shear tests as a function of temperature, were used to investigate the thermal transition of the copolymers. It has been reported that polymer solutions are very sensitive to shear rate around their phase transition [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of hollow fiber spinning, dope viscosity affects the phase inversion process by controlling the solvent and nonsolvent exchange rate. 23 Figure 2 shows the dependence of the logarithmic dope solution viscosities to the reciprocals of the absolute dope solution temperatures for polymer dopes with different PES concentrations. The linear relations between the viscosity and the reciprocal of temperature fit the Arrhenius equation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, thermal kinetics and colloidal stability are influenced by change of temperature. The ultimate ER demeanor depends on the balance procured among these factors [20] [21].…”
Section: The Effect Of Temperature On Shear Stressmentioning
confidence: 99%